2018
DOI: 10.1101/486134
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcranial ultrasound selectively biases decision-making in primates

Abstract: Transcranial focused ultrasound has the promise to evolve into a transformative noninvasive way to modulate activity of neuronal circuits deep in the brain. The approach may enable systematic and causal mapping of how individual brain circuits are involved in specific behaviors and behavioral disorders. Previous studies demonstrated neuromodulatory potential, but the e↵ect polarity, size, and spatial specificity have been di cult to assess. Here, we engaged non-human primates (macaca mulatta) in an established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…It combines non-invasiveness with relatively high (mmscale) spatial resolution and cm-scale penetration depth, not attainable with other therapeutic modalities such as surgical or radio-frequency ablation, deep brain stimulation [6] or transcranial magnetic stimulation [7]. Interestingly, several studies have demonstrated that TUS can remotely modulate neural activity in a range of models including cell cultures [8], rodents [9]- [11], non-human primates [12]- [14] and humans [15], [16], eliciting neuronal stimulation or suppression as well as motor responses. Though several ultrasonic parameters are known to influence neuro-stimulation [10], [11], [17]- [19], as of yet there is no emerging consensus on its underlying physical and physiological mechanisms [10], [20]- [22].…”
Section: Introductionmentioning
confidence: 99%
“…It combines non-invasiveness with relatively high (mmscale) spatial resolution and cm-scale penetration depth, not attainable with other therapeutic modalities such as surgical or radio-frequency ablation, deep brain stimulation [6] or transcranial magnetic stimulation [7]. Interestingly, several studies have demonstrated that TUS can remotely modulate neural activity in a range of models including cell cultures [8], rodents [9]- [11], non-human primates [12]- [14] and humans [15], [16], eliciting neuronal stimulation or suppression as well as motor responses. Though several ultrasonic parameters are known to influence neuro-stimulation [10], [11], [17]- [19], as of yet there is no emerging consensus on its underlying physical and physiological mechanisms [10], [20]- [22].…”
Section: Introductionmentioning
confidence: 99%
“…U LTRASONIC neuromodulation (UNMOD) has gained significant attention in the last decade, because of its capability to modulate brain activity reversibly, non-invasively, selectively, and with high spatial resolution (transversal fullwidth at half maximum in the order of millimeters with a single element focused transducer) [1]- [15]. Furthermore, a good safety profile has been reported [16], [17] and there is no requirement to genetically alter target neurons (cfr.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral data revealed that targeting the left FEF increased the proportion of rightward choices, whereas, stimulation of the right FEF increased the proportion of leftward choices. As an active control, region-specific LI-TUS applied at M1 failed to elicit significant biases in choice behavior (Kubanek et al, 2020).…”
Section: Neuromodulatory Effect Of Tus In Animalsmentioning
confidence: 94%